Antimicrobial resistance of microorganisms present in periodontal diseases: A systematic review and meta-analysis - Abe, Flávia Casale; Kodaira, Katia; Motta, Cristiane de Cássia Bergamaschi; Barberato-Filho, Silvio; Silva, Marcus Tolentino; Guimarães, Caio Chaves; Martins, Carolina Castro; Lopes, Luciane Cruz (Frontiers in Microbiology, 2022)
Objective: The aim of this study was to estimate the antimicrobial resistance in microorganisms present in periodontal diseases. Methods: A systematic review was conducted according to PRISMA statement. The MEDLINE (PubMed/ Ovid), EMBASE, BVS, CINAHL, and Web of Science databases were searched from January 2011 to December 2021 of observational studies which evaluated the antimicrobial resistance in periodontal diseases in permanent dentition. Studies that allowed the antimicrobial consumption until the time of sample collection, studies that used laboratory acquired strains, studies that only characterized the microbial strain present, assessment of cellular morphological changes, sequencing system validation and time series were excluded. Six reviewers, working in pairs and independently, selected titles, abstracts and full texts extracting data from all studies that met the eligibility criteria: characteristics of patients, diagnosis of infection, microbial species assessed, antimicrobials assessed, identification of resistance genes and virulence factors. “The Joanna Briggs Institute” critical appraisal for case series was adapted to assess the risk of bias in the included studies. Results: Twenty-four studies (N= 2.039 patients) were included. Prevotella and Porphyromonas species were the most cited microorganisms in the included studies, and the virulence factors were related to Staphylococcus aureus. The antimicrobial reported with the highest frequency of resistance in the included studies was ampicillin (39.5%) and ciprofloxacin showed the lowest frequency of resistance (3.4%).The most cited genes were related to macrolides. The quality of the included studies was considered critically low. Conclusion: No evidence was found regarding the profile of antimicrobial resistance in periodontal diseases, requiring further research that should focus on regional population studies to address this issue in the era of increasing antimicrobial resistance. Clinical relevance: The knowledge about the present microorganism in periodontal diseases and their respective antimicrobial resistance profiles should guide dentists in prescribing complementary therapy for these infections.